DETERMINATION OF BAS ABOVE-GROUND PART OF PLANTS OF CIRSIUM ARVENSE L. - Nusipali S.K.; Bazhykova K.B. (Academic Scientific Journal of Chemistry, 2019)
The results of the study of the chemical composition of aerial parts of Cirsium arvense L. collected during the fruiting period in the Shamalgan village of Kazakhstan are presented in the article. The quantitative and qualitative composition of biologically active substances was determined. Samples of Cirsium arvense L. contain 3.2% of alkaloids, 2.08% of flavonoids, 4.08% of phenolic acids, 4.5% of hydrocarbons, 1.16% of polysaccharides, 3.8% of terpenoids, 1.2% of organic acids, 3.12% of tannins, 0.78% of coumarins, 14.85% of protein and 1.67% of fat. The variety of biologically active compounds have a biological activity according to our results. A comparative analysis of the mineral, amino and fatty acid composition of Cirsium arvense L. plant was carried out. The analysis of the mineral composition showed the presence of 11 mineral elements: K, Na, Mg, Ca, Cu, Zn, Cd, Pb, Fe, Ni, Mn, which allows us to recommend the studied plants as raw materials rich in macro- and microelements.